2018
DOI: 10.4067/s0717-95022018000200576
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomere Structure: The Importance of Desmin Protein in Muscle Atrophy

Abstract: MARZUCA-NASSR, G. N.; VITZEL, K. F.; MANCILLA-SOLORZA, E. & MÁRQUEZ J. L. Sarcomere structure: The importance of desmin protein in muscle atrophy. Int. J. Morphol., 36(2):576-583, 2018. SUMMARY:Knowing the ultrastructure of skeletal muscle is critical to understand how it works under normal situation and the disorders caused by extreme or pathological conditions. Sarcomere is the basic structural unit of striated muscle tissue. An important element of sarcomere architecture are the intermediate filaments, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
(61 reference statements)
0
8
0
Order By: Relevance
“…This statement was supported by up-regulated DES and VIM in FG relative to those of MG at the later developmental stages. The two genes, also known as the markers for muscle regenerative process, encode intermediate filaments proteins contributing to the sarcomere integrity [ 72 ]. Consistent with our results, Soglia et al [ 14 ] recently reported that the breast muscles of a slow-growing strain expressed lower DES (p = 0.08) and VIM (p = 0.10) if compared with unaffected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…This statement was supported by up-regulated DES and VIM in FG relative to those of MG at the later developmental stages. The two genes, also known as the markers for muscle regenerative process, encode intermediate filaments proteins contributing to the sarcomere integrity [ 72 ]. Consistent with our results, Soglia et al [ 14 ] recently reported that the breast muscles of a slow-growing strain expressed lower DES (p = 0.08) and VIM (p = 0.10) if compared with unaffected broilers.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolysis causes the collapse of the muscle architecture, thus reducing the force generation ability and the force transmission capacity along and across the muscle fiber. As a result, muscles become weak and prone to damage. , Desmin associated atrophy can be explained with two ubiquitin ligases, such as ubiquitin tripartite motif-containing protein 32 (TRIM32) and MURF1. MURF1 catalyzes the breakdown of the thick myosin filament’s proteins, whereas TRIM32 catalyzes the Z-band and the desmin cytoskeleton’s breakdown.…”
Section: Sarcopenia Markersmentioning
confidence: 99%
“…It reduces sarcomere tension range, leading to muscular passive stiffness. The mechanical characteristics of striated muscle (cardiac or skeletal) vary with titin sequence [15]. Titin's main roles are to maintain the thick filament, centre it between the thin filaments, avoid overstretching, and rebound the sarcomere like a spring [16].…”
Section: Introductionmentioning
confidence: 99%